Characterization of a novel OTX2‐driven stem cell program in Group 3 and Group 4 medulloblastoma. Issue 4 (1st March 2018) - Stromecki, Margaret; Tatari, Nazanin; Morrison, Ludivine Coudière; Kaur, Ravinder; Zagozewski, Jamie; Palidwor, Gareth; Ramaswamy, Vijay; Skowron, Patryk; Wölfl, Matthias; Milde, Till; Del Bigio, Marc R.; Taylor, Michael D.; et al.
Abstract : Medulloblastoma (MB) is the most common malignant primary pediatric brain cancer. Among the most aggressive subtypes, Group 3 and Group 4 originate from stem/progenitor cells, frequently metastasize, and often display the worst prognosis, yet we know the least about the molecular mechanisms driving their progression. Here, we show that the transcription factor orthodenticle homeobox 2 (OTX2) promotes self‐renewal while inhibiting differentiation in vitro and increases tumor initiation from MB stem/progenitor cells in vivo . To determine how OTX2 contributes to these processes, we employed complementary bioinformatic approaches to characterize the OTX2 regulatory network and identified novel relationships between OTX2 and genes associated with neuronal differentiation and axon guidance signaling in Group 3 and Group 4 MB stem/progenitor cells. In particular, OTX2 levels were negatively correlated with semaphorin (SEMA) signaling, as expression of 9 SEMA pathway genes is upregulated following OTX2 knockdown with some being potential direct OTX2 targets. Importantly, this negative correlation was also observed in patient samples, with lower expression of SEMA4D associated with poor outcome specifically in Group 4 tumors. Functional proof‐of‐principle studies demonstrated that increased levels of select SEMA pathway genes are associated with decreased self‐renewal and growth in vitro and in vivo and that RHO signaling, known to mediate the effects of SEMA genes, is contributing to the OTX2 KD phenotype. Our study provides mechanistic insight into the networks controlled by OTX2 in MB stem/progenitor cells and reveals novel roles for axon guidance genes and their downstream effectors as putative tumor suppressors in MB. Abstract : We have defined an OTX2‐driven stem cell program and identified a large cohort of unexpected, yet novel, axon guidance gene targets that may be exploited for development of therapies aimed at differentiating the most aggressive medulloblastoma cells. While the genes that regulate axon guidance are well known for their roles in neuronal migration and cell motility, we discovered that these neurodevelopmental cues can regulate the most highly aggressive medulloblastoma stem/progenitor cell populations.